Roman Brooches in Britain A Technological and Typological Study based on the Richborough Collection - Bayley, Justine (Reports of the Research Committee of the Society of Antiquaries of London, 2004)
This work presents the first major analysis of brooches from Roman sites in Britain since the pioneering work of M R Hull in the 1950s and 1960s and is the first to study the material using metallurgical analysis in addition to traditional typological methods. The analytical data for the brooches is available via the Archaeology Data Service: https://archaeologydataservice.ac.uk/archives/view/68fiche/index.cfm